The lnfratumoral choledochojejunostomy for the outlet of transtumoral transhepatic tubes - Estefan, Alberto; Lyonnet, Alberto; di Donna, Bruno; Pérez Billi, lui; Praderi, Raúl (Cirugía del Uruguay, 1984)
Transhepalic transtumoral starting tubes, using a seton, have preved to be best palliative surgical solution for the secondary cholestatic syndrome, al high pedicular obstruction due to tumours that cannot be resected. A new procedure is described to solve or obviate inc,onveniences and eventual complications usually accompanying techniques in use nowadays: the infratumoral choledocho-jejunectomy as a way of withdrawing calibration tubes.